Twenty‐four hours abstinence and the quality of sperm parameters. (24th July 2013) - Lehavi, O.; Botchan, A.; Paz, G.; Yogev, L.; Kleiman, S. E.; Yavetz, H.; Hauser, R.
Summary Patients with abnormal basic parameters and mainly low concentration can be expected to have improved parameters on the second consecutive day. As the number of abnormal basic parameters increases, the more significant improvement can be expected. On the other hand, patients with normal or few abnormal basic semen parameters show a decrease after 24 h. Furthermore, the magnitude of change to both directions in TMC and TNMC values in these patients emphasises these conclusions. Based on the type and mainly the combined number of abnormal basic semen parameters, insemination strategy can be tailored to male fertility patients. Those with abnormal concentration or multiple abnormal semen parameters may benefit from 2 consecutive day intercourses or inseminations or a short period of abstinence due to a significant improvement in the semen parameters on second day insemination. In those with normal basic semen parameters, a reduction in semen quality is expected after 24 h, and a single‐timed insemination and longer abstinence can be recommended.